Pengaruh Return On Asset, Earning Per Share, dan Current Ratio terhadap Harga Saham pada Perusahaan Sektor Otomotif - Ah. Shibghatullah Mujaddidi (Shafin: Sharia Finance and Accounting Journal, 2023)
This study aims to examine and analyze the effect of the current ratio, return on assets and earnings per share on stock prices both partially and simultaneously in Automotive and Component Sector Companies Listed on the Indonesia Stock Exchange for the period 2018-2021. The population used in this study were all 13 companies in the automotive and component sectors using a purposive sampling technique so that 12 companies were selected for 4 years. All samples amounted to 48 financial statements. Methods of data analysis using multiple linear regression with the help of SPSS 24. Based on this study it can be concluded that simultaneously the current ratio, return on assets, and earnings per share have a significant effect simultaneously on stock prices. Partially, the Current Ratio has a significant negative effect on stock prices, Return on Assets has no effect on stock prices, and Earning Per Share has a significant effect on stock prices in automotive and component companies listed on the Indonesia Stock Exchange for the period 2018-2021